Photograph-based diagnosis of burns in patients with dark-skin types: The importance of case and assessor characteristics. Issue 6 (September 2015) - Boissin, C.; Laflamme, L.; Wallis, L.; Fleming, J.; Hasselberg, M.
Highlights On dark-skin types, burn size and depth was accurately diagnosed using photographs. Inter-rater reliability was low, but higher among the SA group and burn surgeons. Intra-rater reliability was high. There was more variability in results for burn size than for burn depth. Case characteristics can affect burn tele-diagnostic accuracy.